2017
DOI: 10.1111/pde.13358
|View full text |Cite
|
Sign up to set email alerts
|

Internal venous anomalies in patients with a genital venous malformation

Abstract: Background: Cutaneous venous malformation (VM) can be associated with internal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
2
6
0
1
Order By: Relevance
“…A study from 2017 determined the frequency of an additional internal vascular anomaly in cases of focal genital venous malformations to be 45% (10 of 22 patients). 18 Despite different inclusion criteria regarding malformation types, our results confirm that approximately 50% of external genital cases also have internal involvement. This suggests that in cases of vascular malformation of the external genitalia, a small externally visible finding is often combined with a larger internal lesion, which can cause substantial health concerns if undetected.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…A study from 2017 determined the frequency of an additional internal vascular anomaly in cases of focal genital venous malformations to be 45% (10 of 22 patients). 18 Despite different inclusion criteria regarding malformation types, our results confirm that approximately 50% of external genital cases also have internal involvement. This suggests that in cases of vascular malformation of the external genitalia, a small externally visible finding is often combined with a larger internal lesion, which can cause substantial health concerns if undetected.…”
Section: Discussionsupporting
confidence: 65%
“…Our findings indicated that 57% of patients (37 of 63) with externally visible malformation signs had additional internal genital involvement. A study from 2017 determined the frequency of an additional internal vascular anomaly in cases of focal genital venous malformations to be 45% (10 of 22 patients) 18 . Despite different inclusion criteria regarding malformation types, our results confirm that approximately 50% of external genital cases also have internal involvement.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Other vascular malformations have also been reported in vascular malformation of the colorectum, such as serosal venous malformation of the cecum and appendix [4] and genital venous malformation [19]. In this study, nine patients (33.3%) had other associated vascular malformations, all of which were not managed.…”
Section: Discussionmentioning
confidence: 67%